Analysis of public management, Psychological work attention, and athletes performance in sport industries - Yu Zhuoyuan, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In this research study, the author looks at China's accomplishments in a range of games or sports. As a country with an increasingly global presence over the past few decades, China’s sports record has drawn the consideration of several games’ specialists and fans. This research study presents an analysis of public management, the psychological work attention and athletes’ performance in the field of sports in China. The present study is based on primary data collected through several specific questions related to psychological work attention and sport performance. The public management and psychological work attention are independent variables and athletes’ performance is identified as a dependent variable. For further data analysis, the study uses STATA software, ANOVA test, graphical test analysis, and the cumulative variables test analysis normally used in this form of research. Results show that there are significant relationships between public management, psychological work attention and athletes’ performance. As of late, there has been a great deal of conversation about the advancement of a sports culture in China and how and why China distinguishes from other nations in this respect. Finally, the investigation concludes with a discussion of the research outcomes as well as recommendations for future research on this subject.